The 2019 International Society of Urological Pathology (ISUP) Consensus Conference on Grading of Prostatic Carcinoma. (August 2020) - van Leenders, Geert J.L.H.; van der Kwast, Theodorus H.; Grignon, David J.; Evans, Andrew J.; Kristiansen, Glen; Kweldam, Charlotte F.; Litjens, Geert; McKenney, Jesse K.; Melamed, Jonathan; Mottet, Nicholas; Paner, Gladell P.; Samaratunga, Hemamali; et al.
Abstract : Five years after the last prostatic carcinoma grading consensus conference of the International Society of Urological Pathology (ISUP), accrual of new data and modification of clinical practice require an update of current pathologic grading guidelines. This manuscript summarizes the proceedings of the ISUP consensus meeting for grading of prostatic carcinoma held in September 2019, in Nice, France. Topics brought to consensus included the following: (1) approaches to reporting of Gleason patterns 4 and 5 quantities, and minor/tertiary patterns, (2) an agreement to report the presence of invasive cribriform carcinoma, (3) an agreement to incorporate intraductal carcinoma into grading, and (4) individual versus aggregate grading of systematic and multiparametric magnetic resonance imaging–targeted biopsies. Finally, developments in the field of artificial intelligence in the grading of prostatic carcinoma and future research perspectives were discussed.